Prior low- or high-intensity exercise alters pacing strategy, energy distribution and performance during a 4-km cycling time trial - Correia Oliveira, C.; Santos, R.; Silva Cavalcante, M.; Bertuzzi, R.; Kiss, M.; Bishop, D.; Lima Silva, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: While it seems clear that pre-exercise, muscle glycogen availability affects the pacing during a time trial (TT), requiring athletes completing a given distance as fast as possible, to date it is not known if selective glycogen depletion of the type I or type II fibers will have different effects on pacing strategy. Therefore, we analyzed the influence of prior exercise designed to predominately reduce muscle glycogen in either type I or II fibers on pacing and performance during a 4-km cycling TT. Methods: After preliminary and familiarization trials, ten amateur cyclists performed three 4-km TT in a randomized, repeated-measures crossover design: 1) TT after an exercise protocol in the evening before (~10 h) designed to reduce glycogen of type I muscle fibers (EX-FIB I); 2) TT after an exercise protocol in the evening before (~10 h) designed to reduce glycogen of type II muscle fibers (EX-FIB II) and; 3) TT without prior evening exercise (CON). Mean values of performance parameters were compared between conditions using repeated-measures ANOVA. A linear mixed model with Bonferroni correction was used to verify the effects of condition and distance or moment on dependent variables. Results: Time to cover 4-km TT and power output (PO) were impaired in EX-FIB I (432.8 ± 8.3 s and 204.9 ± 10.9 W) and EX-FIB II (428.7 ± 6.7 s and 207.5 ± 9.1 W) compared to CON (420.8 ± 6.4 s and 218.4 ± 9.3 W; P<0.05), without difference between EX-FIB I and EX-FIB II (P>0.05). The PO and aerobic contribution were lower in EX-FIB I than in CON at the beginning and middle of the TT (P<0.05). The end-spurt magnitude, anaerobic contribution, and Post-TT plasma lactate were all lower in EX-FIB II than in CONT (-52.5%, -52.2%, -22%, respectively, P<0.05). The integrated electromyography activity was unchanged between conditions (P>0.05). Discussion: Performance was impaired after both protocols, but PO and aerobic contribution at the beginning and middle of trial were more impaired in EX-FIB I, suggesting a reduction in the aerobic metabolism in type I fibers, while the reduced magnitude of the end spurt and anaerobic contribution in EX-FIB II may be attributed to a reduced glycogenolysis in type II fibers. The unchanged electromyography activity suggests that these impairments were related to alterations in peripheral factors. From these findings, it may be suggested that, irrespective of either a prior low- or highintensity exercise, an impairment in overall performance of a 4-km cycling TT is evident, but the pacing adopted, as well as alterations in the energy system distribution, occur in a specific way.